2006
DOI: 10.1161/01.res.0000222059.54917.ef
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Myocardial Contraction by the N-Terminal Domains of Myosin Binding Protein-C

Abstract: Abstract-Myosin binding protein-C (MyBP-C) is a poorly understood component of the thick filament in striated muscle sarcomeres. Its C terminus binds tightly to myosin, whereas the N terminus contains binding sites for myosin S2 and possibly for the thin filament. To study the role of the N-terminal domains of cardiac MyBP-C (cMyBP-C), we added human N-terminal peptide fragments to human and rodent skinned ventricular myocytes. At concentrations Ͼ10 mol/L, the N-terminal C0C2 peptide activated force production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
98
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 37 publications
17
98
3
Order By: Relevance
“…This mechanism could explain observations that C0C2 activates thin-filament motility in vitro (14). It could also explain force development in sarcomeres in low Ca 2ϩ (31) and the apparent increased Ca 2ϩ sensitivity of cross-bridge cycling (5,32). The predicted overlap of binding sites for C0 and C1 and tropomyosin under low-Ca 2ϩ conditions suggests that cMyBP-C may interact more strongly with the thin filament at high Ca 2ϩ (33) or in the presence of strongly bound cross-bridges, i.e., when the thin filament is fully activated and cross-bridge-binding sites are completely uncovered.…”
Section: Discussionmentioning
confidence: 82%
“…This mechanism could explain observations that C0C2 activates thin-filament motility in vitro (14). It could also explain force development in sarcomeres in low Ca 2ϩ (31) and the apparent increased Ca 2ϩ sensitivity of cross-bridge cycling (5,32). The predicted overlap of binding sites for C0 and C1 and tropomyosin under low-Ca 2ϩ conditions suggests that cMyBP-C may interact more strongly with the thin filament at high Ca 2ϩ (33) or in the presence of strongly bound cross-bridges, i.e., when the thin filament is fully activated and cross-bridge-binding sites are completely uncovered.…”
Section: Discussionmentioning
confidence: 82%
“…This could increase the freedom of movement of Tm so that single S1 binding events are no longer significantly inhibited. Physiological experiments in which N-terminal fragments of cMyBP-C are diffused into skinned myocytes (46,47) also demonstrate activation of contraction at low (relaxing) Ca 2+ concentrations. In these experiments, it was suggested that cMyBP-C affects crossbridge cycling primarily by binding to myosin, thus affecting myosin crossbridge mechanics, although mechanisms involving actin binding were also considered possible.…”
Section: Discussionmentioning
confidence: 93%
“…Previous modeling suggested that the C0 and C1 domains could clash with Tm in its blocked position (25,27,28), whereas experiments in which expressed N-terminal fragments were added to skinned cardiac myocytes implicated the ProAla-rich domain between C0 and C1 in modulating Ca 2+ activation of crossbridge cycling (46). However, in similar skinned fiber experiments, the ProAla-rich domain was found to have no effect, whereas the C1 and M-domains were critical to the Ca 2+ -sensitizing and activating effects of various N-terminal domains (48).…”
Section: Discussionmentioning
confidence: 99%
“…Fiber studies using N-terminal domain fragments at high stoichiometric concentrations demonstrate that the addition of the C1-C2 or C0-C2 peptide results in a leftward shift in the pCa-tension curve with or without the presence of native cMyBP-C [18][19][20]. When the C0 domain of MyBP-C was deleted in a transgenic model, again a leftward shift in fiber pCatension relation was observed [8].…”
Section: Introductionmentioning
confidence: 98%